Gut microbiome alterations and their clinical and biological implications in ovarian cancer: a systematic review - Zhang, Beibei; Mohd Sahardi, Nur Fatin Nabilah; Chew, Kah Teik; Di, Wen; Shafiee, Mohamad Nasir (Frontiers in Oncology, 2025)
BackgroundIncreasing evidence shows the that gut microbiome (GM) plays a crucial role in ovarian cancer (OC) progression, offering potential avenues for microbiome-based intervention strategies. However, research in this area remains limited. This systematic review aimed to synthesize current evidence on microbiome composition and diversity in OC, focusing on its association with disease diagnosis, postoperative changes, and responses to chemotherapy or PARP inhibitor (PARPi) therapy.MethodsA literature search was performed in PubMed and Web of Science up to October 2025 using keywords: (gut microb* OR gut bacteri* OR intestinal microb* OR intestinal bacteri*) AND (ovarian cancer OR ovarian carcinoma OR carcinoma of ovary). Only original research articles involving human subjects were included. Data on GM alterations in OC patients, postoperative changes, and responses to chemotherapy or PARP inhibitor (PARPi) therapy were extracted and analysed. ResultsNine eligible studies, comprising longitudinal and case-control studies were reviewed. At diagnosis, OC patients displayed gut dysbiosis characterised by an increase in Proteobacteria and a decrease in Firmicutes. Genus-level analysis revealed lower levels of Akkermansia and elevated levels of Bacteroides and Prevotella, suggesting disrupted microbial homeostasis. Following surgery, both Firmicutes and Proteobacteria declined, indicating significant microbiome shifts. During chemotherapy, especially neoadjuvant treatment, Firmicutes re-emerged as the dominant phylum. Family-level analyses identified increased Coriobacteriaceae and decreased Ruminococcaceae. Platinum-sensitive patients demonstrated more stable GM profiles than those with platinum resistance Genera such as Angelakisella, Arenimonas, and Roseburia emerged as potential candidates for diagnostic or prognostic markers of chemotherapy resistance. Meanwhile, Phascolarbacterium is identified as a PARPi response in BRCA1/2-negative OC, with higher levels linked to longer progression-free survival. ConclusionThis review highlights a dynamic GM composition in OC across disease stages and treatments, underscoring the need for further research on microbiome-targeted therapeutic strategies.